2020
DOI: 10.3390/ijerph17124422
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Social Interactions in the Development of an Extracurricular University Volunteer Activity in a Developing Country

Abstract: The relevance of participating in structured extracurricular activities (ECA from here onwords) in higher education is increasing. Involvement in these activities helps students develop personal and social skills that positively affect academic and professional training, well-being, and the development of attitudes toward community involvement. This study analyzes the role of social interactions in the perceived benefits of students, who have participated in an ECA in a developing country. Moreover, this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…The investigations were conducted in seven countries: three in Spain ( Díaz-Iso et al, 2020 ; Fernández et al, 2020 ; Luque-Suárez et al, 2021 ), two in the United Kingdom ( Mayew et al, 2020 ; Defeyter et al, 2021 ), and one in Germany ( Paulus et al, 2021 ), Taiwan ( Dutta et al, 2021 ), Israel ( Martin et al, 2020 ), the United States of America ( Vatovec and Ferrer, 2019 ), and Sweden ( Bälter et al, 2018 ). Most studies included students in higher education (as it was an inclusion criterion), however, Bälter et al’s (2018) investigation included also nine teachers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigations were conducted in seven countries: three in Spain ( Díaz-Iso et al, 2020 ; Fernández et al, 2020 ; Luque-Suárez et al, 2021 ), two in the United Kingdom ( Mayew et al, 2020 ; Defeyter et al, 2021 ), and one in Germany ( Paulus et al, 2021 ), Taiwan ( Dutta et al, 2021 ), Israel ( Martin et al, 2020 ), the United States of America ( Vatovec and Ferrer, 2019 ), and Sweden ( Bälter et al, 2018 ). Most studies included students in higher education (as it was an inclusion criterion), however, Bälter et al’s (2018) investigation included also nine teachers.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the authors’ approaches were fundamentally quantitative, with questionnaire searching as data collecting instrument ( Fernández et al, 2020 ; Mayew et al, 2020 ; Defeyter et al, 2021 ; Dutta et al, 2021 ; Luque-Suárez et al, 2021 ; Paulus et al, 2021 ), and four employed a mixed methods approach, where other instruments were used alongside the questionnaires, such as interviews ( Bälter et al, 2018 ; Díaz-Iso et al, 2020 ), life experiences ( Martin et al, 2020 ), and intervention reports ( Vatovec and Ferrer, 2019 ). Table 1 displays the results and provides an overview of the research found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las dimensiones evaluadas en esta investigación, son similares a los constructos encontrados por Severino-González et al (2020). Los resultados indican que los estudiantes universitarios expresan una mayor responsabilidad social en relación a la dimensión Planteamiento del ejercicio profesional desde la perspectiva del compromiso social, lo que está en correspondencia con el voluntariado universitario (Díaz-Iso et al, 2020). Esto se relaciona con los resultados obtenidos por Barajas et al (2020), particularmente con los hallazgos que dan cuenta del reconocimiento de los compromisos que deben tener los futuros profesionales con la sociedad, en búsqueda del bien común del territorio y la comunidad en general.…”
Section: Discussionunclassified
“…Los beneficios del voluntariado universitario favorecen el replanteamiento social de sus educandos debido a las diversas acciones realizadas en alguna comunidad en particular o, bien en algún grupo específico de personas, dotando a los educandos de habilidades personales y sociales (Díaz-Iso et al, 2020), gracias al aprendizaje experiencial y vinculadas a actividades curriculares y extracurriculares. Todo lo cual, fortalece la sensibilidad social y la capacidad en generar vínculos como consecuencia del abordaje de preocupaciones sociales (Chiva-Bartoll et al, 2020); conduciendo al desarrollo de competencias que permiten abordar alguna problemática sanitaria, política y medioambiental (Joseph y Carolissen, 2019;Chawłowska et al, 2021).…”
Section: Introductionunclassified